2014
DOI: 10.1016/j.bbamem.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of indole NH hydrogen bonding in the organization and dynamics of gramicidin channels

Abstract: The linear ion channel peptide gramicidin represents an excellent model for exploring the principles underlying membrane protein structure and function, especially with respect to tryptophan residues. The tryptophan residues in gramicidin channels are crucial for the structure and function of the channel. In order to test the importance of indole hydrogen bonding for the biophysical properties of gramicidin channels, we monitored the effect of N-methylation of gramicidin tryptophans, using a combination of ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 81 publications
(141 reference statements)
1
18
0
Order By: Relevance
“…One such example is the aforementioned M2 proton channel, wherein the N-H ends of the key Trp41 residues, according to a recent high-resolution crystal structure, 37,38 point toward the aqueous pore, leaving the benzene rings facing the hydrocarbons of the lipid. Another example is the gramicidin A proton channel, 39,40 where H-bonding interactions involving the N-H groups of several Trp residues are believed to be crucial for stabilizing the functional channel conformation. A third example is transmembrane peptides and proteins, where Trp residues are often located at the water-membrane interface with their N-H groups H-bonded to either water or a lipid headgroup.…”
Section: Resultsmentioning
confidence: 99%
“…One such example is the aforementioned M2 proton channel, wherein the N-H ends of the key Trp41 residues, according to a recent high-resolution crystal structure, 37,38 point toward the aqueous pore, leaving the benzene rings facing the hydrocarbons of the lipid. Another example is the gramicidin A proton channel, 39,40 where H-bonding interactions involving the N-H groups of several Trp residues are believed to be crucial for stabilizing the functional channel conformation. A third example is transmembrane peptides and proteins, where Trp residues are often located at the water-membrane interface with their N-H groups H-bonded to either water or a lipid headgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Put together, our fluorescence measurements suggest that Trp140 resides in a hydrophobic environment, and is micelle solvated. Trp76, however, is rigid and in a polar, solvent‐accessible environment [37]. Although structurally similar, location in dissimilar environments affects indole interaction with the surrounding micelles, and may confer different functionalities to OmpX indoles.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for micelle solvation of Trp140 is obtained from the average lifetime (< τ >) measurements [36,37], which reveals an unusually long lifetime of 4.6 ns for OmpX:W140 (Table 1). Solvent‐accessible tryptophans undergo non‐radiative losses and possess short lifetimes [22], as seen for Trp76.…”
Section: Resultsmentioning
confidence: 99%
“…Chaudhuri et al. reported the importance of indole NH hydrogen bonding in gramicidin channels, in which methylation of the indole of NH disrupts the hydrogen bonding, resulting in the loss of membrane conformation . Our group previously reported that the indole NH group can also be involved in hydrogen bonding to neighboring molecules, which is little reported in the literature .…”
Section: Introductionmentioning
confidence: 83%